The role of gratitude on stress and psychological wellbeing among parent of children with cancer in Aceh - Marty Mawarpury; Diana Setya Ningsih; Sri Rezeki (INSPIRA: Indonesian Journal of Psychological Research, 2023)
Cancer is a disease with a high incidence that pediatric patients need parents during treatment. The situation became a source of stress for parents. One way to deal with stress is to be grateful that the psychological wellbeing of the caregivers who accompany children with cancer is maintained. This study aims to determine the relationship between stress and psychological wellbeing with the moderation of gratitude in the parents of children with cancer in Aceh. This study used a quantitative approach, involving 14 participants at the shelter for children with cancer undergoing treatment in Banda Aceh aged 20–40 years. Participants were selected using the non-probability sampling method and the incidental sampling technique. Individual stress levels were measured using the Perceived Stress Scale, wellbeing using the Warwick-Edinburgh Mental Wellbeing Scale, and gratitude using the Indonesian Grateful Scale. The data were analyzed using the Rank Spearman nonparametric test, showing no relationship between stress and psychological wellbeing, but there is a relationship between stress and gratitude and gratitude with psychological wellbeing. This result shows partially that gratitude has a relationship with stress and psychological wellbeing. It means that with gratitude, stress can be controlled and impacts the psychological wellbeing of parents accompanying children with cancer.